The role of women in maintaining health and preserving culinary in Malay Batubara society through the tradition of Menotou Banjo - Hasnidar; Robert Sibarani; Silvana Sinar; Mulyadi (Elsevier, 2021)
Objective: This study discusses the role of Batubara Malay women in maintaining health and preserving culinary through the Menotou Banjo tradition. The Menotou Banjo tradition is a tradition of growing rice in the Malay community in Batubara Regency, North Sumatra Province. Method: The research method used, namely qualitative with interactive models. The interactive model uses four stages, namely data collection, data condensation, data display, and conclusions: drawing/verifying. The research approach used is a Anthropolinguistics. Results: The results showed the role of Batubara Malay women in maintaining the health of themselves and their families through healthy food during the rice planting season. The serving of food and cakes during the implementation of the Menotou Banjo tradition is a symbol of the ability and skills of the Batubara Malay woman in gathering almost the same food into various types of food. In addition, Batubara Malay women also have a high social and mutual cooperation in social life. Conclusion: The conclusion of the research shows that the Batubara Malay woman has an important role in maintaining health and also helps her husband to earn a living for family survival. Thus the next generation of healthy, prosperous, and intelligent people will be created.